2011
DOI: 10.1017/s0950268811001233
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of dog rabies control in Limpopo province (South Africa)

Abstract: Rabies is a prevalent and re-emerging disease in South Africa particularly in rural areas with high human densities. Outbreaks are frequently reported in the north and eastern parts of this country, probably an indication of inadequacy in the control of the disease. Following the 2005/2006 outbreak in Limpopo, we undertook an analysis of case surveillance data and genetically characterized 18 rabies viruses, all recovered from domestic dogs. Although rabies prevalence gradually declined annually from 2007, dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…canine distemper may not be so prevalent in southern Africa. In fact, rabies was a major cause of death in Zimbabwe [43] and in the South African Limpopo province where also two thirds of submitted jackals tested positive for rabies [49]. A very high rate was also found for kudus (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…canine distemper may not be so prevalent in southern Africa. In fact, rabies was a major cause of death in Zimbabwe [43] and in the South African Limpopo province where also two thirds of submitted jackals tested positive for rabies [49]. A very high rate was also found for kudus (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…18,26 Since 2004, the disease has emerged in locations where it was controlled before, as is evident by outbreaks in Vhembe district of Limpopo province, Ehlanzeni district of Mpumalanga province, the Bojanala Platinum district of North West province and the Botshabelo surroundings in Free State province. 27,28,29,30 In addition, a great number of outbreaks of dog rabies were reported in Soweto, Gauteng province, in 2010, marking the first report of sustained dog-to-dog transmission of the rabies virus in this province. 31 The locations described here are mostly densely populated, which further raises the concerns of the possibility of the human rabies cases occurring considering the close association of dog rabies outbreaks and human cases.…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, the first reported cases of rabies occurred in 1902 (38). Dog rabies is now widespread throughout Africa wherever there are dog populations of sufficient density, except in certain areas of sub-Saharan Africa, where rabies is maintained in specific carnivorous wildlife species (41,44,45,46,47). The advent of molecular epidemiology and virus-typing techniques in the early 1980s demonstrated that the establishment of rabies among wild carnivores was one of the most significant consequences of the long-term maintenance of rabies cycles (38,44,45,48,49,50).…”
Section: History Of Rabies In Africamentioning
confidence: 99%